Novel Hybrid Process for the Conversion of Microcrystalline Cellulose To Value-Added Chemicals: Part 1: Process Optimization - Akın, Okan; Yüksel, Aslı; Yüksel Özşen, Aslı (Springer Verlag, 2016)
In this paper, a novel hybrid process for the treatment of microcrystalline cellulose (MCC) under hot-compressed water was investigated by applying constant direct current on the reaction medium. Constant current range from 1A to 2A was applied through a cylindrical anode made of titanium to the reactor wall. Reactions were conducted using a specially designed batch reactor (450 mL) made of SUS 316 stainless steel for 30–120 min of reaction time at temperature range of 170–230 °C. As a proton donor H2SO4 was used at concentrations of 1–50 mM. Main hydrolysis products of MCC degradation in HCW were detected as glucose, fructose, levulinic acid, 5-HMF, and furfural. For the quantification of these products, High Performance Liquid Chromatography (HPLC) and Gas Chromatography with Mass Spectroscopy (GC–MS) were used. A ½ fractional factorial design with 2-level of four factors; reaction time, temperature, H2SO4 concentration and applied current with 3 center points were built and responses were statistically analyzed. Response surface methodology was used for process optimization and it was found that introduction of 1A current at 200 °C to the reaction medium increased Total Organic Carbon (TOC) and cellulose conversions to 62 and 81 %, respectively. Moreover, application of current diminished the necessary reaction temperature and time to obtain high TOC and cellulose conversion values and hence decreased the energy required for cellulose hydrolysis to value added chemicals. Applied current had diverse effect on levulinic acid concentration (29.9 %) in the liquid product (230 °C, 120 min., 2 A, 50 mM H2SO4). © 2016, Springer Science+Business Media Dordrecht.
Keywords: Cellulose; Hydrothermal electrolysis; Levulinic acid; Sub-critical water; 5-HMF; Hydrothermal electrolysis; Biomass